Lactobacillus rodentium sp. nov., from the digestive tract of wild rodents - Killer, J; Havlík, J; Vlková, Eva; Rada, V; Pechar, R; Benada, O; Kopečný, J; Kofroňová, O; Sechovcová, H (International journal of systematic and evolutionary microbiology, 2014)
Three strains of regular, long, Gram-stain-positive bacterial rods were isolated using TPY, M.R.S. and Rogosa agar under anaerobic conditions from the digestive tract of wild mice (Mus musculus). All 16S rRNA gene sequences of these isolates were most similar to sequences of Lactobacillus gasseri ATCC 33323T and Lactobacillus johnsonii ATCC 33200T (97.3% and 97.2% sequence similarities, respectively). The novel strains shared 99.2-99.6% 16S rRNA gene sequence similarities. Type strains of L. gasseri and L. johnsonii were also most related to the newly isolated strains according to rpoA (83.9-84.0% similarities), pheS (84.6-87.8%), atpA (86.2-87.7%), hsp60 (89.4-90.4%) and tuf (92.7-93.6%) gene sequence similarities. Phylogenetic studies based on 16S rRNA, hsp60, rpoA, atpA and pheS gene sequences, other genotypic and many phenotypic characteristics (results of API 50 CHL, Rapid ID 32A and API ZYM biochemical tests; cellular fatty acid profiles; cellular polar lipid profiles; end products of glucose fermentation) showed that these bacterial strains represent a novel species within the genus Lactobacillus. The name Lactobacillus rodentium sp. nov. is proposed to accommodate this group of new isolates. The type strain is MYMRS/TLU1T (=DSM 24759T=CCM 7945T).
Keywords: Animals; mastné kyseliny; Lactobacillus; Fatty Acids; DNA bakterií; bakteriální geny; Intestine, Small; peptidoglykan; RNA, Ribosomal, 16S; DNA, Bacterial; Rectum; Molecular Sequence Data; hybridizace nukleových kyselin; Mice; fermentace; myši; zastoupení bazí; Phylogeny; Peptidoglycan; molekulární sekvence - údaje; Czech Republic; Base Composition; Bacterial Typing Techniques; Fermentation; Sequence Analysis, DNA; Nucleic Acid Hybridization; techniky typizace bakterií; Česká republika; Genes, Bacterial; zvířata; sekvenční analýza DNA; fylogeneze; rektum; RNA ribozomální 16S; tenké střevo